(untitled) (IIUC Business Review, 2022)
This study is conducted to examine the effects of market share on profitability. A panel data covering 8 full-fledged Islamic banks of Bangladesh and the period 2011-2020 is used for the analysis. Based on Hausman test, random effects model is chosen to estimate the effects of market share. Market share is represented in terms of asset as well as deposit. To measure profitability, return on equity is used. Investment is used as control variable. Time dummies are also used to account for time effects. Findings suggest that one percentage point increase in market share in terms of asset leads to 3.73 percentage points increase in ROE. Besides, if market share in terms of deposit increases by one percentage point, ROE increases by 3.14 percentage points. Based on these findings, Islamic banks of Bangladesh should consider increase in market share as one of the effective ways to enhance profitability. IIUC Business Review Vol. 9, Dec. 2020 pp. 103-110